Degradation of Cd, Cu, Fe, Mn, Pb and Zn by Moringa-oleifera, zeolite, ferric-chloride, chitosan and alum in an industrial effluent - Jagaba, A.H. (Ain Shams University, 2021)
Coagulation-flocculation constitute the backbone process in most water and wastewater treatment plants. This study focused on determining the optimum coagulant dose for moringa oleifera seed extract, zeolite, ferric chloride, chitosan and aluminium sulphate coagulants through the coagulation, flocculation and sedimentation process. It also ascertain which coagulant has the potential for higher removal of Cd, Cu, Fe, Mn, Pb and Zn. The test was conducted with initial pH, settling time, coagulant aid dose, rapid mixing speed & time, slow mixing speed & time as constant parameters. The determination of heavy metals concentration in POME was carried out using an Inductively Coupled Plasma (ICP) and an Atomic Absorption Spectrometer (AAS). The process efficiency was assessed in terms of percentage removals for the heavy metals examined. The results proved that chitosan, FeCl3, alum, zeolite and moringa oleifera had the concentrations of 400, 2000, 1000, 1000, and 4000 mg/L as the optimum dosage respectively. Â© 2020 THE AUTHORS